A randomised, controlled study of rate versus rhythm control in patients with chronic atrial fibrillation and heart failure: (CAFÉ-II Study). Issue 11 (11th March 2009) - Shelton, R J; Clark, A L; Goode, K; Rigby, A S; Houghton, T; Kaye, G C; Cleland, J G F
Abstract : Background: Atrial fibrillation (AF) and heart failure (HF) often coexist. The aim was to investigate whether restoring sinus rhythm (SR) could improve cardiac function, symptoms, exercise capacity and quality of life (QoL) in patients with chronic heart failure. Methods: Patients with HF and persistent AF receiving guideline-recommended treatments, including anticoagulants, were eligible for the study. Patients were randomised to either rhythm (treated with amiodarone for at least 3 months prior to attempting biphasic external cardioversion and continued amiodarone long-term if SR was restored) or rate control. Anticoagulants were continued throughout the study regardless of rhythm, unless contraindications developed. Both groups were treated with beta blockers and/or digoxin to reduce the heart rate to <80 bpm at rest and <110 bpm after walking. Symptoms, walk distance (6-minute corridor walk test, 6MWT), QoL and cardiac function were assessed at baseline and 1 year. Results: 61 patients with HF and persistent AF (median duration 14 months (IQR 5 to 32)) were randomly assigned to a rate or rhythm control strategy. Of patients assigned to rhythm control (n = 30), 66% were in SR at 1 year, and 90% of those assigned to rate control (n = 31) achieved the heart rate target. At 1 year, NYHA class (p = 0.424) and 6MWT distance (p = 0.342) were similar between groups but patients assigned to rhythm control had improved LV function (p = 0.014), NT-proBNP concentration (p = 0.046) and QoL (p = 0.019) compared with those assigned to rate control. Greatest improvement was seen in patients in whom SR was maintained. Conclusion: Restoring SR in patients with AF and heart failure may improve QoL and LV function when compared with a strategy of rate control.